Oronyms and hydronyms in “Baburnama” - Kenzhalin К.К.; Daniyar А.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
Zahir al-din Babur is a ruler who united the Mughal tribes in one hand, the founder of the Mughal dynasty in India, a descendant of Genghis Khan, the eldest son of Omar Sheikh, an outstanding warrior, poet and genius, statesman. Babur is not only a person well versed in literature, art, history, military and state affairs, but also the best in ecology, geography, biology, the author made consistent explanations and definitions of the objects of nature of his time -– water, air, soil, mountains, flora and fauna. Babur gives accurate references in written sources about his habitat, starting from Central Asia, passing through mountains and passes, rivers and lakes in Afghanistan and India. That is, «Baburnama» has a lot of examples of oronyms and hydronyms from a toponymic point of view. This article provides a geographical definition of various mountain ranges and hills, rivers and lakes, and streams encountered on the paths of Babur.